A conceptual paper on the benefits of a non-governmental search and rescue organization - Wengelin, M.; de Wet, T. (Biomechanics and Medicine in Swimming XI, 2010)
This conceptual paper aims at discussing the characteristics of and differences between modern Western independent SAR institutions and the initiatives that have been taken in developing countries. It highlights the benefits of the non-governmental SAR organization, not only to provide search and rescue capacity, but also to be a vehicle of progress and change.